Generation of Leukemia Inhibitory Factor and Basic Fibroblast Growth Factor-Dependent Induced Pluripotent Stem Cells from Canine Adult Somatic Cells - Luo, Jiesi (Mary Ann Liebert, Inc., 2011)
For more than thirty years, the dog has been used as a model for human diseases. Despite efforts made to develop canine embryonic stem cells, success has been elusive. Here, we report the generation of canine induced pluripotent stem cells (ciPSCs) from canine adult fibroblasts, which we accomplished by introducing human OCT4, SOX2, c-MYC, and KLF4. The ciPSCs expressed critical pluripotency markers and showed evidence of silencing the viral vectors and normal karyotypes. Microsatellite analysis indicated that the ciPSCs showed the same profile as the donor fibroblasts but differed from cells taken from other dogs. Under culture conditions favoring differentiation, the ciPSCs could form cell derivatives from the ectoderm, mesoderm, and endoderm. Further, the ciPSCs required leukemia inhibitory factor and basic fibroblast growth factor to survive, proliferate, and maintain pluripotency. Our results demonstrate an efficient method for deriving canine pluripotent stem cells, providing a powerful platform for the development of new models for regenerative medicine, as well as for the study of the onset, progression, and treatment of human and canine genetic diseases.